Cost-Effectiveness of Ticagrelor for Acute Coronary Disease to Prevent Cardiovascular Events in Three Hospitals in Indonesia - At Thobari, Jarir; Krisdinarti, Lucia; Nugroho, Dhite; Haposan, Jonathan; Firdaus, Isman; Suryandani, Rr. Arum Ramadhyan; Munawar, Muhammad; Agung, Jimmy (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Acute coronary syndromes (ACS) are life-threatening CVD associated with Indonesia's significant health and economic burdens. The study objective was to evaluate the cost-effectiveness of ticagrelor in reducing CV endpoint in the Indonesia setting. Methods: Markov model was used as a decision analysis to compare ticagrelor with clopidogrel. We constructed decision tree model included four health conditions (no additional events, non-fatal myocardial infarction, non-fatal stroke, and any cause death), The probability of each state and quality-adjusted life years were derived from the PLATO trial and Indonesia life table. The outcome's resource consumption and associated costs were collected from three hospitals (public, national referral, and private hospitals) in Indonesia. The study used 5 years and lifetime horizon and discounting rate of 3%. Results: The incremental QALYs and life-year gained (LYG) of ticagrelor in five years was 0.0410 and 0.0462, respectively; in a lifetime was 0.0828, and 0.0947, respectively. The ICER per QALY of ticagrelor versus clopidogrel in private, national referral, and public hospitals was USD 2390.276, USD 3813.638, USD 1278.361, respectively for five years; and USD 2471.392, USD 5453.987, USD 2343.269, respectively for a lifetime. The probability of ticagrelor to be cost-effective was about 66.6% on a five-year and 99.7% on a lifetime with WTP USD 3634. Conclusion: Compared to the clopidogrel, QALYs and life-year gained of use ticagrelor higher. The incremental cost-effectiveness ratio in five years and lifetime model showed under one-time GDP, it means the use of ticagrelor was vastly cost-effective and acceptable to apply in the Indonesian clinical setting.